Pengaruh Destinasi Pariwisata Pulau Komodo Terhadap Beberapa Aspek Pembangungan Di Kabupaten Manggarai Barat - Mustamin H. Idris; Sel va; Rizky Destari (Universitas Muhammadiyah Mataram, 2019)
Tourism is one sector that plays a role in the development process in contributing to the region and society. One of the tourist destinations that are currently in great demand by tourists is the Komodo Island Tourism Destination, which is one of the mainstay of tourism potential in the city of Labuan Bajo. Komodo is one of the step animal species that still lives in this modern era and was chosen as one of the seven wonders of the world. The purpose of this study was to find out how the influence of Komodo Island Travel Destinations on several aspects of development in the city of Labuan Bajo. The research method is applied by applying quantitative descriptive, data collection techniques, including interviews, observation and documentation. In particular, this research was conducted in the city of Labuan Bajo with the active participation of 41 key informants. The results of the study revealed that the policy of the Office of Tourism and Culture in the city of Labuan Bajo was well run and quite successful, the Regional Original Income increased for 5 consecutive years and fulfilled the welfare of the communities around Komodo Island Tourism Destinations.